SIBER, INFORMASI, DAN KEPEMIMPINAN ERA DIGITAL: TRANSFORMASI SUMBER DAYA TEKNOLOGI DALAM DOKTRIN PERTAHANAN INDONESIA - Evi Bayu Priatno; Hendra Saputra, Tarsisius Susilo, Nurhidayat, Tuwadi (INTELIGENSIA MEDIA, 2026)
The digital era has introduced a new domain of warfare: cyberspace and information. Major powers such as Russia, the United States, and Israel demonstrate how visionary leadership in cyberspace can transform technology into strategic defense capabilities. Russia integrates cyberattacks and disinformation as geopolitical tools, the U.S. has established the Defend Forward doctrine alongside broad public–private partnerships, while Israel, through Unit 8200, embeds cyber operations into every military campaign. Indonesia, facing rising threats such as massive data breaches and disinformation campaigns, urgently needs a distinctive national cyber defense doctrine. This article analyzes global leadership models, assesses Indonesia’s existing gaps, and proposes a cyber defense framework grounded in Pancasila and TNI’s values of struggle. Findings suggest that without doctrinal reform, Indonesia risks becoming a soft target in global cyber warfare. However, through transformational leadership and proactive policies, Indonesia can transform technological resources into a resilient digital defense shield, aligned with the vision of Indonesia Emas 2045.